2012
DOI: 10.1155/2012/290854
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tissue Inhibitor of Metalloproteinase-1 in Breast Cancer

Abstract: Introduction. Despite advances in breast cancer systemic treatment, new prognostic and predictive factors are still needed. Tissue inhibitor of metalloproteinase-1 (TIMP-1), a physiologic inhibitor of matrix metalloproteinases (MMPs), can act in both pro- and antitumoral effects. As role of TIMP-1 in breast cancer is controversial, we aimed to determine the prognostic significance of TIMP-1 in breast cancer. Methods. A single center-based case-control study was applied. Primary breast cancers from women with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
0
22
2
Order By: Relevance
“…Interestingly, the samples with metastasis in this study showed a tendency to an increased expression of TIMP-1 in comparison with samples from patients without metastasis. Those results must be considered a tendency, since they had not statistically significant support; anyway this fact is mentioned, because other authors [22, 23] previously reported elevated TIMP-1 in association with metastasis, suggesting that the tendency observed in our studies is perhaps real (and statistics could be easily corrected increasing the number of samples). In the interim, we have not enough evidence to support this molecule as a participant in the occurrence of metastasis in ductal breast cancer.…”
Section: Resultscontrasting
confidence: 56%
“…Interestingly, the samples with metastasis in this study showed a tendency to an increased expression of TIMP-1 in comparison with samples from patients without metastasis. Those results must be considered a tendency, since they had not statistically significant support; anyway this fact is mentioned, because other authors [22, 23] previously reported elevated TIMP-1 in association with metastasis, suggesting that the tendency observed in our studies is perhaps real (and statistics could be easily corrected increasing the number of samples). In the interim, we have not enough evidence to support this molecule as a participant in the occurrence of metastasis in ductal breast cancer.…”
Section: Resultscontrasting
confidence: 56%
“…17,48 In our study; although TIMP-1 overexpression was associated with poor response to NAT, this did not lead to a significant prognostic value.…”
Section: Discussioncontrasting
confidence: 57%
“…5,36,58,59 Finally, other studies reported no correlation between TOP2a gene amplification or overexpression and survival rate. 48,60,61 Patients who attain a complete response may experience long-term survival or be cured of the disease; and the pCR rate is one of the good prognostic factors independent of the initial tumor stage and other prognostic markers. 62 We proved that TOP2a overexpression is associated with favorable response to anthracycline-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular phenotypes have become increasingly valuable in guiding treatment decisions. However, these markers remain imperfect tools and, therefore, new prognostic and predictive factors are still required to optimize treatments among BC patients [5].…”
Section: Introductionmentioning
confidence: 99%